2020
DOI: 10.1007/s11661-020-05674-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Powder Recycling on Defect Formation in Electron Beam Melted Alloy 718

Abstract: The extent to which powder recycling can be permitted before risking a loss in performance of critical components is a major aspect for the viability of electron beam melting (EBM). In this study, the influence of powder oxidation during multi-cycle EBM processing on the formation of oxide-related defects in Alloy 718 is investigated. The amount of defects and their distribution in samples produced from virgin and re-used powder is studied by means of image analysis and oxygen measurements. Morphological analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…As observed in earlier studies, [3,26,29] during the actual melting process, there is a risk of transferring of nonmetallic phases (mainly Al-rich oxide and TiN) from the powder to the components. Furthermore, since these phases tend to accumulate into larger sized clusters or oxide flakes, they act as potential damage initiation sites, especially under cyclic loading conditions.…”
Section: Discussionmentioning
confidence: 61%
“…As observed in earlier studies, [3,26,29] during the actual melting process, there is a risk of transferring of nonmetallic phases (mainly Al-rich oxide and TiN) from the powder to the components. Furthermore, since these phases tend to accumulate into larger sized clusters or oxide flakes, they act as potential damage initiation sites, especially under cyclic loading conditions.…”
Section: Discussionmentioning
confidence: 61%
“…Such accumulation of inclusions has already been reported for Alloy 718 produced by other AM processes. Gruber et al [28] revealed the transport and accumulation of oxide and nitride inclusions, which cluster in the liquid metal, at the top and side surfaces of components built by EBM. As a result, a refining effect was proposed explaining almost a 50% reduction in oxygen content in the EBM-produced compact compared to the feedstock powder, which is valid even in case of powder re-use after 30 cycles [28].…”
Section: Discussionmentioning
confidence: 99%
“…Gruber et al [28] revealed the transport and accumulation of oxide and nitride inclusions, which cluster in the liquid metal, at the top and side surfaces of components built by EBM. As a result, a refining effect was proposed explaining almost a 50% reduction in oxygen content in the EBM-produced compact compared to the feedstock powder, which is valid even in case of powder re-use after 30 cycles [28]. It should be emphasized that TiN and Al 2 O 3 are expected to float in the liquid metal because of their low densities in comparison to the metal matrix (i.e., TiN: 5.4 g/cm 3 , Al 2 O 3 : 4.0 g/cm 3 , Alloy 718: 8.2 g/cm 3 ) [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For better energy efficiency and to circumvent the smoking effect, a high vacuum in the chamber to minimize electron beam attenuation and preheating of the powder bed to semi-sintering temperature to enhance the electronic conductivity of the powder bed are prerequisites of EBM [2,3]. Although preheating at elevated temperatures and high vacuum can improve the process stability, these processing conditions can affect the unused feedstock powder in the build chamber [4][5][6].…”
Section: Introductionmentioning
confidence: 99%